Facile synthesis of a Ag/MoS2 nanocomposite photocatalyst for enhanced visible-light driven hydrogen gas evolution. Issue 8 (21st August 2015) - Cheah, A. J.; Chiu, W. S.; Khiew, P. S.; Nakajima, H.; Saisopa, T.; Songsiriritthigul, P.; Radiman, S.; Hamid, M. A. A.
<x xml:space="preserve">Abstract</x> Ag-decorated MoS2 nanocomposite photocatalyst with enhanced visible-light driven hydrogen gas evolution performance.